456 CD39 T Cells With Low PD-1 Expression are Markers for Durable Immunotherapy Response to Anti-PD-1 in Murine Glioblastoma. (April 2023) - Choi, John; Pant, Ayush; Kim, Young-Hoon; Routkevitch, Denis; Jackson, Christopher Mitchell; Jackson, Christina; Kim, Lily H.; Lim, Michael
Abstract : INTRODUCTION: Clinical trials investigating anti-PD-1 therapy for glioblastoma (GBM) have failed to demonstrate increased overall survival, unlike in other cancers such as non-small cell lung cancer (NSCLC). Despite the immunosuppressive characteristics of GBM, a small subset of patients in these trials have shown durable anti-PD-1 response. Recently, CD39+ T cells have been implicated as infiltrating lymphocytes that, once activated, demonstrate robust anti-tumor activity. Understanding the unique immunosuppressive milieu of GBM including this cell population may help elucidate why some patients show treatment response. METHODS: Mice orthotopically implanted with GL261 had blood collection prior to anti-PD-1 exposure with t-SNE mapping of T cells. The molecular profiles of mice with long-term survival were compared with those that did not. Due to a lack of GBM patient samples that have shown immunotherapy response, we examined whether these molecular patterns recapitulated in the blood of NSCLC patients responded to anti-PD-1. RESULTS: The blood of long-term survivor mice implanted with GBM demonstrated a significantly greater proportion of CD39+ CD8 T cells with low PD-1 expression (PD-1lo) with subsequent increased representation of this population in the tumor as well (P < 0.05). This CD39+ CD8+ PD-1lo population was also highly represented in the blood of treatment-naÏve NSCLC patients who responded to anti-PD-1 (P < 0.05). Furthermore, once exposed to anti-PD-1 in vivo, this CD39+ CD8+ PD-1lo population showed high immune activity with robust IFN-y expression (P < 0.05). CONCLUSIONS: Mice with CD39+ CD8+ PD-1lo T cells are strongly associated with anti-PD-1 response. This has implications for exploring this cell population as a blood biomarker and an active anti-tumor population that may be mobilized with adoptive cell transfer and CAR-T cell strategies.